2x-5(4-x)=x(x+7)

Simple and best practice solution for 2x-5(4-x)=x(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5(4-x)=x(x+7) equation:


Simplifying
2x + -5(4 + -1x) = x(x + 7)
2x + (4 * -5 + -1x * -5) = x(x + 7)
2x + (-20 + 5x) = x(x + 7)

Reorder the terms:
-20 + 2x + 5x = x(x + 7)

Combine like terms: 2x + 5x = 7x
-20 + 7x = x(x + 7)

Reorder the terms:
-20 + 7x = x(7 + x)
-20 + 7x = (7 * x + x * x)
-20 + 7x = (7x + x2)

Add '-7x' to each side of the equation.
-20 + 7x + -7x = 7x + -7x + x2

Combine like terms: 7x + -7x = 0
-20 + 0 = 7x + -7x + x2
-20 = 7x + -7x + x2

Combine like terms: 7x + -7x = 0
-20 = 0 + x2
-20 = x2

Solving
-20 = x2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x2' to each side of the equation.
-20 + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
-20 + -1x2 = 0

Add '20' to each side of the equation.
-20 + 20 + -1x2 = 0 + 20

Combine like terms: -20 + 20 = 0
0 + -1x2 = 0 + 20
-1x2 = 0 + 20

Combine like terms: 0 + 20 = 20
-1x2 = 20

Divide each side by '-1'.
x2 = -20

Simplifying
x2 = -20

Reorder the terms:
20 + x2 = -20 + 20

Combine like terms: -20 + 20 = 0
20 + x2 = 0

The solution to this equation could not be determined.

See similar equations:

| 5a-1+a=7 | | 3(n-4)=5(n+2) | | -3n=-4.2 | | 9y+2=11y-7 | | 2x-10+44=8x | | 4r+6=1 | | 23=9y-5y | | 20+3x-15+x=25 | | 2*-4-5*2=10 | | 3pq+2p^2= | | 5x^2-7=1-x | | y/3=33 | | 30/120=x/100 | | 3*6-4*-7=5 | | 5/x=20/100 | | (3-6y)-(3+7y)= | | 9=-5-m | | -4+5=-16 | | (2w-1)(w)=55 | | 30-2N=2N-2 | | 24x^2-10x-6=0 | | 4*-2+5*-1=-13 | | 4x-1=2(5-3x) | | 5y-32x=5 | | 30=-8x | | 71.14=64.75+0.03m | | 7x+3+x=16+13 | | 1/2(g-4)=6 | | 12p=2(m-p)+8 | | 5=3*1+2 | | 27-5*y=83 | | 7/5-3/4 |

Equations solver categories